COMPARED TO THE STRAIGHT LINK TO THE STATISTICAL MODEL AND ARTIFICIAL NEURAL NETWORKS(APPLIED STUDY) - Hamadi, Saleema (Iraqi Journal of Science, 2024)
Canonical correlation as agenral method instating the relation tow groubs of variables,which are regarded more grneral infields of scince ,and we chose of apply them on the accounting.Department in the college of administrator and economcas/university of Baghdad in the practical part. It has been chose the student performance in four years gradudates 2003-2002 from where degrees classes from thirteeth dewasslass four after cancilling material culture national order to know the performance of the student through the four years and the possibility to reduce waist in educational system whether in training powers and other reguirements to reach a top valuables scientific level with aless possible expenditures and assuming theirs performance using the model of canonical correlation analysis and artificial neural network model to reach and comperare the result ln tow models to get a best model. artificial neural network model part theory of network in operation research.